< Basic Algebra < Exponential Functions
Vocabulary
Lesson
Example Problems
Ex.1
(c+3)(c-2)-(c+2)(c-3)=
(c²-2c+3c-6)-(c²-3c+2c+6)=
c²-2c+3c-6-c²+3c-2c-6=
Answer: 2c-12
Ex.2
3(2s+4)(s-3)-2(s+3)(2s-4)=
(6s+12)(s-3)-(2s+6)(2s-4)=
(6s²-18s+12s-36)-(4s²-8s+12s-24)=
(6s²-6s-36)-(4s²+4s-24)=
6s²-6s-36-4s²-4s+24=
Answer: 2s²-10s-12
Practice Problems
Use ^
for exponentiation
This article is issued from Wikibooks. The text is licensed under Creative Commons - Attribution - Sharealike. Additional terms may apply for the media files.